The morphological affinity of the Early Pleistocene footprints from Happisburgh, England, with other footprints of Pliocene, Pleistocene, and Holocene age. Issue 144 (July 2020) - Wiseman, Ashleigh L.A.; Stringer, Chris B.; Ashton, Nick; Bennett, Matthew R.; Hatala, Kevin G.; Duffy, Sarah; O'Brien, Thomas; De Groote, Isabelle
Abstract: Fossil hominin footprints provide a direct source of evidence of locomotor behavior and allow inference of other biological data such as anthropometrics. Many recent comparative analyses of hominin footprints have used 3D analytical methods to assess their morphological affinities, comparing tracks from different locations and/or time periods. However, environmental conditions can sometimes preclude 3D digital capture, as was the case at Happisburgh (England) in 2013. Consequently, we use here a 2D geometric morphometric approach to investigate the evolutionary context of the Happisburgh tracks. The comparative sample of hominin tracks comes from eight localities that span a broad temporal range from the Pliocene to Late Holocene. The results show disparity in the shapes of tracks ascribed to hominins from the Pliocene (presumably Australopithecus afarensis ), Pleistocene (presumably Homo erectus and Homo antecessor ), and Holocene ( Homo sapiens ). Three distinct morphological differences are apparent between time samples: changes in adduction of the hallux, changes in the shape and position of the medial longitudinal arch impression, and apparent changes in foot proportions . Linear dimensions classified the potential H. antecessor tracks from Happisburgh as being most similar to the presumed H. erectus prints from Ileret. We demonstrate using 2D geometric morphometric methods and linear dimensions that the Happisburgh tracks are morphologically similar to other presumed Homo tracks and differ from the Laetoli footprints. The probable functional implications of these results fit well with previous comparative analyses of hominin tracks at other sites.